Remote Sensing applications for effective fire disaster management plans: A review - Ferrelli, Federico (2023)
The current context of climate change and imminent global warming is leading to changes in temperature and rainfall patterns worldwide that affect soil moisture, vegetation, and soil conditions, the incidence of dry and wet events, and consequently, the occurrence, intensity, and magnitude of fires. Fires harm people’s quality of life as they can disrupt economic activities and affect public health. Additionally, fires damage the environment, accelerating water and wind erosion processes, altering air quality, and contributing to ecosystem degradation. Pampas in Argentina was selected as an example to study fires at a regional scale using remote sensing techniques due to its status as one of the most fertile plains in the world and the country’s most densely populated area. The fires are carefully analyzed and described considering three stages: i) pre-fires, ii) fires, and iii) post-fires. Afterwards, fire disaster management plans are described to assess these events, reduce their impacts on society and biodiversity, and minimize the ecosystems’ recovery time. In this sense, this manuscript aims to review the relationships between climate change, global warming, and the occurrence of fires. Additionally, it proposes to analyze the potential of remote sensing in analyzing these events at a regional scale to provide the mechanisms and tools necessary for formulating fire disaster management plans.